Al-Taḥlīl al-Manhajī lil-Kitāb al-Taʿlīmī "Al-Lughat al-ʿArabiyyah" lil-Ṣaff al-Rābiʿ al-Ibtidāʾī - Nugroho, Ikhsan Pebdwi; Basid, Abdul; Nasaruddin, Nasaruddin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This research aims to determine the extent to which Arabic textbooks for the fourth grade of elementary schools are suitable in terms of their suitability to the 2013 curriculum. To achieve this goal, this study uses descriptive research methods. The approach used in this research is qualitative, using the literature study method. We collected the data for this research by reviewing existing documents. The data from this research includes fourth-grade elementary school Arabic language textbooks, their contents, and the educational curriculum. The data was analyzed by looking at what was in the book and how it related to the curriculum. This was done to see how closely the teaching materials from the fourth-grade Arabic language book put out by the Ministry of Religion of the Republic of Indonesia were in line with the 2013 Curriculum. The study's results indicate that the Ministry of Religion of the Republic of Indonesia's fourth-grade Arabic language book, published at the school level, aligns with the 2013 curriculum, offering a range of teaching materials suitable for use in the Arabic language teaching process at the elementary school level. ined and enriched further to improve it, including religious elements in the topics presented, which need to be enriched to increase students' knowledge.